2016
DOI: 10.4236/jep.2016.712145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quality for the Egyptian Red Sea Coastal Waters during 2011-2013

Abstract: To assess the quality of the Egyptian Red Sea coastal waters for the sustainable use and development, due to its importance for the national income, four field campaigns were annually carried out during the period from 2011-2013 to investigate the hydrography, nutrient salts, heavy metals and petroleum hydrocarbons. Except for the area of Bir Shalatein, the results of beach litter cleared out that the shoreline of the studied area is not affected by man-made litter. No sewage could be observed. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 38 publications
3
13
2
Order By: Relevance
“…It ranged between 12.39 mg/l at St. 1 during 2018 and 21.50 mg/l at St. 12 during 2019, with averages of 16.33 ± 3.12 and 17.24 ± 3.15 mg/l during 2018 and 2019, respectively. The TSM concentrations reported in this work were very close to the previous study in the Red Sea coast ( Fahmy et al, 2016 , Heba et al, 2004 ). The TSM ranged from 1.08 to 38.11 mg/l, while it showed lower concentrations than those reported by Heba et al (2004) (TSM ranged from 10 to 440 mg/l).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It ranged between 12.39 mg/l at St. 1 during 2018 and 21.50 mg/l at St. 12 during 2019, with averages of 16.33 ± 3.12 and 17.24 ± 3.15 mg/l during 2018 and 2019, respectively. The TSM concentrations reported in this work were very close to the previous study in the Red Sea coast ( Fahmy et al, 2016 , Heba et al, 2004 ). The TSM ranged from 1.08 to 38.11 mg/l, while it showed lower concentrations than those reported by Heba et al (2004) (TSM ranged from 10 to 440 mg/l).…”
Section: Resultssupporting
confidence: 91%
“…The surface of the Red Sea is about 437,000 square kilometers, with an average depth of 490 m. The Red Sea is famous for its marine life and coral. The number of invertebrates on the Red Sea is higher than 1000 species, with 200 soft and hard coral reefs ( Hassan et al, 2002 , Fahmy et al, 2016 ). Seawater quality has a major concern, with safety and accessibility, throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…4(B)] showed the highest antiviral activity (92.51%) which is in a good agreement with many previous studies [16]. Seaweeds, especially the genus Gracilaria and sargassium are the most attractive candidate that has the anti-HIV activities [23] because of its stability to achieve high yields and producing commercially valuable extracts. It has been concluded that sessile marine organism (sponge and seaweeds) contain substances capable of potent biological activity which has also been demonstrated against different types of cancer and HIV/AIDS [27].…”
Section: Specialized Screening Bioassayssupporting
confidence: 91%
“…The deep-sea anoxic brines of the Red sea are one of the most extreme environments on the earth in comparison to overlying seawater. The anoxic brines are characterized by high salinity (increased from 4% up to 26%), high temperature (up to 70°C), increased concentration of heavy metals, and decrease in O 2 levels [23] Therefore, marine-derived seaweeds bioactive secondary metabolites have the ability to tolerate and survive in these extreme conditions, since they are uniquely equipped with some self-defenses [1][2][3][4]20].…”
Section: Broad Biochemical Drug Discovery Bioassaymentioning
confidence: 99%
“…The growing increase in Egyptian population, as well as urbanization expansion; lead to a corresponding increase in industrial, agriculture, urban effluents that discharged into the aquatic environment of Egypt [8][9][10][11][12][13][14][15], leading to water quality deterioration. Poor quality water can lead to water borne diseases as well as death of aquatic life [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%